Ecotourism Policy Research Trends in Indonesia, Japan, and Australia - Saraswati Sisriany; Katsunori Furuya (Jurnal Manajemen Hutan Tropika, 2020)
Numerous definitions and concepts regarding ecotourism lead to different implementations in ecotourism policies and systems. Identifying trends between countries provide valuable information for the development of inadequate ecotourism sites. This study aimed to understand the trends in ecotourism policies in Japan, Indonesia, and Australia by examining the bibliographic records of existing ecotourism policy research. These records were retrieved from the Scopus database and processed by using the scientometrics analysis. The results show the significant research trends of ecotourism policy in each country based on the co-occurrence of keywords were "conservation" for Indonesia, "biodiversity" for Japan, and "management" for Australia. Whereas, based on the research field, it revealed a similar priority within ecotourism policy between Australia and Japan in Social Science, while Indonesia in Environmental Science. The pattern of the keyword network analysis results in an anomaly in Indonesia compared to Japan and Australia, which clarifies the overlapping problem in ecotourism policy in Indonesia. It also visualized the shifting trends of research in some timeline intervals and notifies their relation to the emerging of ecotourism policy. This research also included the usefulness of the research results for future study and the recommendation for the ecotourism policy, especially for Indonesia.